A community training scheme in cardiopulmonary resuscitation. Issue 6417 (25th February 1984) - Vincent, R; Martin, B; Williams, G; Quinn, E; Robertson, G; Chamberlain, D A
Abstract : Community instruction in basic life support and resuscitation techniques has been offered in Brighton Health District since 1978. Classes are held frequently for the general public and businesses, schools, and other organisations. First aid care for unconscious patients, the treatment of respiratory obstruction or failure, and the recognition and management of cardiac arrest is taught in a single two hour session. Over 20 000 people have been taught, up to 40 at a time in multiple groups of six to eight, by lay instructors usually supervised by ambulancemen trained to "paramedic" standards. Fifty four incidents have been reported to us in which techniques learnt in the classes have been implemented. Five patients recovered after first aid support but subsequently did not seek medical treatment. Of the 34 patients reviewed in hospital, at least 20 survived to be discharged. We believe that intervention may have been life saving in 16 instances. The benefit of cardiopulmonary resuscitation for victims who may have been asystolic is, however, difficult to quantify because the outcome without intervention cannot be predicted accurately. Community training in basic life support should be considered in association with ambulances equipped for resuscitation and hospital intensive care and cardiac care units as an integrated service for the victims of sudden circulatory or respiratory emergencies. The results achieved so far in Brighton and in other more advanced schemes, particularly in the United States of America, may encourage other health authorities to adopt similar programmes.